2019
DOI: 10.1080/21691401.2019.1665058
|View full text |Cite
|
Sign up to set email alerts
|

Cilostazol ameliorates high free fatty acid (FFA)-induced activation of NLRP3 inflammasome in human vascular endothelial cells

Abstract: Cardiovascular disease is recognized as a leading cause of death worldwide, but the risk of death is 2-3 times higher for individuals with diabetes. NLRP3 inflammasome activation is a leading pathway of vascular damage, and new treatment methods are needed to reduce NLRP3 inflammasome expression, along with a detailed understanding of how those treatments work. In a series of assays on human vascular endothelial cells that were exposed to high concentrations of free fatty acids (FFA) to induce a diabetes-like … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…A recent T A B L E 2 Changes in carotid ultrasonography findings, ankle-brachial index, and microcirculation after cilostazol or aspirin treatment study showed the potential of cilostazol as an effective treatment for diabetic endothelial dysfunction and vascular disease by reducing inflammasome activity. 42 These data support the contention that improvement in vascular function can be expected after cilostazol treatment.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…A recent T A B L E 2 Changes in carotid ultrasonography findings, ankle-brachial index, and microcirculation after cilostazol or aspirin treatment study showed the potential of cilostazol as an effective treatment for diabetic endothelial dysfunction and vascular disease by reducing inflammasome activity. 42 These data support the contention that improvement in vascular function can be expected after cilostazol treatment.…”
Section: Discussionsupporting
confidence: 66%
“…The PORH was slightly increased in the CTZ group, while it exhibited a decreasing tendency in the ASA group, leading to a borderline significant difference between the two groups. A recent study showed the potential of cilostazol as an effective treatment for diabetic endothelial dysfunction and vascular disease by reducing inflammasome activity 42 . These data support the contention that improvement in vascular function can be expected after cilostazol treatment.…”
Section: Discussionmentioning
confidence: 57%
“…Cilostazol significantly reduces NLRP3 inflammasome activation and the activity of NOX4, TXNIP, HMGB1, IL-1β, and IL-18 in HAECs induced with FFA. Cilostazol also protected the function of SIRT1, which serves to limit the activity of NLRP3 inflammasome 102 .…”
Section: Hypoglycemic Agentsmentioning
confidence: 99%
“…Interestingly, the deletion of endothelial TXNIP in mice or in vivo anti-TXNIP treatment protects from oxidative stress and NLRP3 inflammasome activation [13,21]. Metformin or other compounds are also used to lower TXNIP aortic levels in vivo or endothelial levels in vitro in order to restrain NLRP3 activation and protect from endothelial dysfunction and cardiovascular risk factors [60,67,87,[91][92][93][94][95][96][97][98][99][100][101]. The regulation of the NLRP3 inflammasome by the TRX-TXNIP complex is believed to be controlled by Nrf2 and AMPK [60,[102][103][104]106,107].…”
Section: Txnip: Link Between Oxidative Stress and Inflammationmentioning
confidence: 99%